2018
DOI: 10.1002/jmri.26298
|View full text |Cite
|
Sign up to set email alerts
|

PET/MRI in Breast Cancer

Abstract: View this article online at wileyonlinelibrary.com.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 91 publications
1
19
0
Order By: Relevance
“…investigated the diagnostic performance of 18F-FDG PET/MRI for hepatic metastases in a diverse group of patients with primary malignancy. Similar to the results in this systematic review, they found very good diagnostic accuracy for the detection of hepatic metastases with a patient-level meta-analytic summery sensitivity of 99.2% and specificity of 98.6% [ 11 , 26 , 48 ]. Especially in subcentimeter hepatic metastases, the reported sensitivity of 18F-FDG PET/MRI outperforms that achieved by 18F-FDG PET/CT [ 48 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…investigated the diagnostic performance of 18F-FDG PET/MRI for hepatic metastases in a diverse group of patients with primary malignancy. Similar to the results in this systematic review, they found very good diagnostic accuracy for the detection of hepatic metastases with a patient-level meta-analytic summery sensitivity of 99.2% and specificity of 98.6% [ 11 , 26 , 48 ]. Especially in subcentimeter hepatic metastases, the reported sensitivity of 18F-FDG PET/MRI outperforms that achieved by 18F-FDG PET/CT [ 48 ].…”
Section: Discussionsupporting
confidence: 81%
“…Theoretically, 18F-FDG PET/MRI could offer an attractive one-stop-shop solution for patients with locally advanced breast cancer with affected axillary lymph nodes who should undergo both breast MRI for locoregional staging and whole-body 18F-FDG PET/CT for nodal and distant staging. 18F-FDG PET/MRI could then subsequently be used to assess the response to NST [ 11 , 12 ]. Moreover, using 18F-FDG PET/MRI for breast cancer staging allows the possibility to perform diffusion-weighted imaging (DWI) as part of the MRI protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) is both a morphological and functional imaging tool and is the most sensitive technique to date for breast cancer screening (29). DCE-MRI is frequently used in breast cancer staging and treatment monitoring (30). Integrated PET/MRI, which can acquire both metabolic data and high-contrast morphological images in a single exam, has recently been used more often in breast cancer patients.…”
Section: Pet/mrimentioning
confidence: 99%
“…Although sentinel lymph node (SLN) mapping and biopsy are routinely applied to evaluate lymph-node metastases of breast cancer, imaging techniques are utilized as additional modalities in nodal assessment. Most studies have indicated that PET-based imaging is more sensitive in detecting axillary metastases than MRI (30). Figure 3 shows an example of the imaging lymph-node metastasis in a 66-year-old female patient with right breast cancer by PET/CT and MRI.…”
Section: Imaging the Lymph-node Metastasesmentioning
confidence: 99%
“…Synchronized multiparametric 18 F-uoro-2-deoxy-d-glucose ( 18 F-FDG) PET/MRI is a novel imaging technique that combines multiparametric morphologic and functional information from MRI with metabolic information provided by PET offering unique insights into tumor biology to achieve the ultimate goal of precision medicine in oncology [7,8]. Recent data support the use of 18 F-FDG PET/MRI in breast cancer patients for different diagnostic purposes [9,10]. Initial data using the combination of separately acquired MRI and PET data indicate an improvement in the differentiation of benign and malignant breast lesions [11], but at present the role of synchronized multiparametric 18 F-FDG PET/MRI for breast cancer diagnosis has not been fully assessed.…”
Section: Introductionmentioning
confidence: 99%